A Theological Review Of Evangelism And Its Influence On Church Growth - David Neyland Sumarauw; Hery Budi Yosef; Endang Pasaribu; Guntur Hamonangan Sahat Silaban (Jurnal Impresi Indonesia, 2025)
Evangelism is one of the fundamental aspects of Christian theology that aims to spread the good news of Christ. As the times evolve, evangelism faces various challenges, including secularization, social change, and technological developments that affect the way the church reaches the people. In this context, the theological understanding of evangelism and its impact on church growth is a relevant issue to be studied. This study aims to examine the theological review of evangelism and analyze how evangelism contributes to the growth of the church. In addition, the study also identifies evangelistic strategies that are relevant to the global context and challenges of the church today. This study uses a qualitative approach with a literature study method. Data were collected from a variety of academic sources, including theological journals, missiology books, and Bible studies. The analytical techniques used are descriptive-qualitative, which aims to understand the relationship between evangelism and church growth based on relevant theological and empirical sources. The results of the study show that evangelism has a significant impact on the growth of the church, both in terms of the number of congregations and spiritual depth. The various evangelistic methods that have been applied in the history of the church, such as personal evangelism, mass evangelism, and the use of digital media, have different effectiveness depending on the social and cultural context. In addition, discipleship as part of evangelism has proven to be an important factor in maintaining the sustainability of church growth. This research contributes to the development of a more contextual and strong theology-based evangelistic strategy. The church in the modern era needs to adapt a more inclusive and digital-based approach to evangelism without eliminating its theological values.